Acute-on-Chronic Kidney Injury in Thyroid Hormone Withdrawal: A Case with Possible Implications for Radioactive Iodine Planning. (16th August 2015) - McAninch, Elizabeth A.; Lagari, Violet S.
Abstract : The association between renal dysfunction and hypothyroidism is of increasing clinical importance as thyroid hormone replacement may attenuate decline in renal function and improve cardiovascular outcomes in patients with chronic kidney disease (CKD). Although multiple mechanisms for the induction of renal insufficiency in hypothyroidism have been described, the renal impact of short-term, acute hypothyroidism is unknown, which has possible implications for thyroid cancer patients preparing to receive radioactive iodine (RAI). A 56-year-old gentleman with history of unilateral renal agenesis and CKD stage III presented with intermediate-risk papillary thyroid cancer. In preparation for RAI, he underwent thyroid hormone withdrawal (THW) associated with acute kidney injury (AKI), as marked by a decrease in his estimated GFR from 53 to 32 mL/min/1.73 m 2 . Upon resumption of thyroid hormone, renal function returned to baseline within months. Although AKI in this case was not otherwise associated with adverse outcome and reversed upon resumption of thyroid hormone, it is possible that this phenomenon could result in potential harm, particularly in the patient with baseline renal insufficiency. In CKD patients, preparation for RAI therapy may require special consideration; future studies should address the role of recombinant TSH to mitigate deleterious renal effects of acute hypothyroidism in this setting.